Patellar Instability after Total Knee Arthroplasty - Swartz, Gabrielle; Abdo, Zuhdi E.; Bains, Sandeep S.; Dubin, Jeremy A.; Hameed, Daniel; Nandi, Sumon; Mont, Michael A.; Delanois, Ronald E.; Scuderi, Giles R. (The Journal of Knee Surgery, 2025)
Patellar instability following total knee arthroplasty (TKA) is a rare, yet serious complication, potentially requiring revision surgery or resulting in chronic dysfunction. When encountered, it is paramount to understand the etiologies, diagnostic approaches, treatment options, and outcomes of the selected treatment. The most common cause of patella instability is improper positioning of components, leading to lateral maltracking of the patella. Factors such as internal rotation and/or medialization of femoral or tibial components and lateralization of the patellar button have been identified as factors that contribute to instability. Additionally, a longstanding valgus deformity of the knee may exacerbate patella maltracking. Patients typically present with anterior knee pain, worsened by activities like stair climbing, and may report sensations of giving way. Radiographs and computed tomography scans aid in evaluating component positioning and rotation. Operative intervention is often necessary, with options ranging from soft tissue realignment to component revision. Lateral retinacular release is a common approach, although it is associated with complications such as osteonecrosis of the patella. Proximal or distal realignment procedures may be required if instability persists. Some recent case reports have also described medial patellofemoral ligament reconstruction as a treatment modality, but more investigation on the topic is still pending. It is important that the treatment strategy address the underlying cause, as failure to do so may result in recurrent instability. The best way to avoid patella instability is to pay attention to all the details of component position and soft tissue balance during the index procedure.
Keywords: total knee arthroplasty; complications; management